Pengaruh Return On Asset (ROA), Return On Equity (ROE), Current Ratio (CR) terhadap Harga Saham pada Perusahaan yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018 - Teresia Sri Arihta; Dhea Cristina Damanik; Susi Hannaria Manalu; Rafida Khairani (Ekonomis: Journal of Economics and Business, 2020)
This study aims to determine and examine the influence of the variable Return On Assets, Return On Equity, and Current Ratio on Stock Prices simultaneously or partially, and also to see what variables have a very big influence on the stock prices of wholesale companies in the Trade sector. and Investment. The data processed is secondary data in the form of a summary of the financial statements of 15 manufacturing companies in the Wholesale sector of the Trade and Investment sector from 2015 to 2018. The method used in conducting this research is the classical assumption test and multiple linear regression method using SPSS version 20.00. The test hypothesis used in this study is t-statistic and F-statistic at the 5% significance level. Testing that is sourced from the simultaneous regression coefficient test means that the Return on Assets, Return On Equity, and Current Ratio simultaneously can have a major influence on stock prices. Meanwhile, partially it can be interpreted that there is a significant influence between Return On Assets on stock prices in wholesale manufacturing companies in the Trade and Investment sector. And does not have a partial effect between Return On Equity and Current Ratio on stock prices in wholesale manufacturing companies in the Trade and Investment sector.